High resolution modelling of valley cold pools. (14th June 2013) - Vosper, Simon; Carter, Emilie; Lean, Humphrey; Lock, Adrian; Clark, Peter; Webster, Stuart
Abstract: The Met Office Unified Model has been adapted to run with a 100 m horizontal grid length for a region of complex terrain whose valleys are too narrow to be represented in the operational forecast (1.5 km grid length) model. Forecasts of temperatures are compared with observations from the COLd air Pooling EXperiment. The model provides a realistic representation of valley cold pools which form during stable nights, although the predictions are shown to be sensitive to vertical resolution. Reducing the vertical grid spacing near the surface results in lower night‐time temperatures and larger, more realistic, valley–hill temperature contrasts.